Mangrove Conservation Based Strategy in Ecotourism Development as Part of “Banyuurip Mangrove Centre’’ Coastal Resources Management in Gresik Regency, East Java, Indonesia - Umi Zakiyah; Woro Wuninggar (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2024)
Banyuurip Mangrove Center (BMC) is a form of mangrove ecosystem conservation and utilization in Banyuurip Village that still faces obstacles in its ecotourism sector management. This study aims to determine the condition of mangroves in BMC, identify Internal Factor Analysis Summary (IFAS) and External Factor Analysis Summary (EFAS), and develop the best strategies for BMC management based on its mangrove condition. This research uses a survey method that includes the data obtained from respondents and the in-situ data on mangrove conditions. Analysis of mangrove data includes identification of species, density, and relative density. Meanwhile, data from the respondents, including tourists and management staff, were analyzed using SWOT analysis. Based on research results, it was known that mangroves in BMC are in relatively good condition. From the respondent questionnaire using SWOT analysis, the best strategy to be suggested is the SO strategy. These strategies must include government support by maximizing its advantages, utilizing social media for promotion, developing mangrove nurseries to produce quality mangrove seedlings, collaborating with Perlindungan Masyarakat (LINMAS) or Community Protection to improve security, and their economic sector by involving the society in another factor of the ecotourism management such as mangrove processing.